DIVERSITY OF MANHAJ IN ḤADĪTH CODIFICATION: A COMPARATIVE STUDY OF THE METHODOLOGIES OF ḤADĪTH BOOK COMPILATION FROM THE FIRST CENTURY TO THE CONTEMPORARY ERA - Andi Indar Wulan; Siti Salma Saludi; Zaenab (JOURNAL OF QUR'AN AND HADITH STUDIES, 2026)
This article examines the diverse methodological approaches (manāhij) employed in the compilation of ḥadīth books as a foundational element of the Islamic scholarly tradition. Despite the breadth of existing scholarship on ḥadīth sciences, no unified comparative framework systematically accounts for the full spectrum of compilation methodologies from primary codification through derivative and elaborative genres. This gap limits researchers’ ability to navigate the ḥadīth corpus with methodological precision. Employing a historical-descriptive approach combined with a structured literature review, this study traces the development of ḥadīth codification across five historical phases, from the era of oral transmission in the first century of the Hijri calendar to the digital revolution of the contemporary period. As its primary contribution, this article proposes a tripartite taxonomic framework classifying twelve methodologies Jāmiʿ, Muṣannaf, Sunan, Ṣaḥīḥ, Musnad, Muʿjam, Mustakhraj, Mustadrak, Aṭrāf, Sharḥ, Mukhtaṣar, and Zawāʾid  into primary, derivative, and elaborative categories. Through comparative analysis, the findings reveal a fundamental trade-off between authenticity and accessibility: Ṣaḥīḥ compilations offer the highest authentication guarantee but cover a restricted corpus, whereas Musnad and Muṣannaf compilations prioritize comprehensiveness and biographical depth at the expense of critical selectivity. These methodological variations are not merely technical; they embody distinct epistemological orientations reflecting each compiler’s scholarly purpose and pedagogical intent. The tripartite framework offers researchers a systematic tool for source selection in contemporary ḥadīth studies and carries significant implications for curriculum development in Islamic higher education and for engagement with expanding digital ḥadīth resources.